2021
DOI: 10.1177/0896860821990528
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of culture-directed antibiotics for the treatment of peritonitis in automated peritoneal dialysis: A systematic narrative review

Abstract: The objectives of this study were to provide a summary of the pharmacokinetic data of some intraperitoneal (IP) antibiotics that could be used for both empirical and culture-directed therapy, as per the ISPD recommendations, and examine factors to consider when using IP antibiotics for the management of automated peritoneal dialysis (APD)-associated peritonitis. A literature search of PubMed, EMBASE, Scopus, MEDLINE and Google Scholar for articles published between 1998 and 2020 was conducted. To be eligible, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Several studies 15 17 have demonstrated that frequent and rapid exchanges in APD are likely to result in greater peritoneal drug clearance, and extrapolation of antibiotics dosing from CAPD to APD may result in significant under-dosing. 1 Furthermore, our recent systematic review 4 concluded that the limited available PK data for IP antibiotics in APD might not be valid in patients receiving variable APD regimens. It highlighted that patient-related factors, particularly the presence of residual kidney function and different stages of the peritoneal inflammation during peritonitis episodes, could also affect the PK of IP antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 15 17 have demonstrated that frequent and rapid exchanges in APD are likely to result in greater peritoneal drug clearance, and extrapolation of antibiotics dosing from CAPD to APD may result in significant under-dosing. 1 Furthermore, our recent systematic review 4 concluded that the limited available PK data for IP antibiotics in APD might not be valid in patients receiving variable APD regimens. It highlighted that patient-related factors, particularly the presence of residual kidney function and different stages of the peritoneal inflammation during peritonitis episodes, could also affect the PK of IP antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic dosing recommendations are primarily based on pharmacokinetic (PK) studies in patients on continuous ambulatory peritoneal dialysis (CAPD), 2 while data on automated peritoneal dialysis (APD) remain scarce. 3,4 Although the ISPD recommendations have raised concerns over the potential under-dosing of antibiotics in patients on APD, no specific recommendations were made to treat peritonitis in this group of patients. Substantial variations in the outcomes of peritonitis have been reported within Australia 5 ; this may be related in part to the variability in practice on how peritonitis is treated in patients on APD.…”
Section: Introductionmentioning
confidence: 99%
“…As a clinical challenge that often causes organ damage and death, LPS-induced peritonitis is associated with factors such as peritoneal dialysis, sepsis, and pathogenic microbial infections [ 2 , 3 , 4 ]. Although some encouraging progress has been achieved, its mechanism of action is still not fully elucidated [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a series of treatment progressions have been achieved, the mortality rate caused by peritonitis and its complications is still rising [ 1 ]. Based on the cause of its occurrence, peritonitis can be divided into aseptic peritonitis, bacterial peritonitis, peritoneal dialysis-related peritonitis, and LPS (lipopolysaccharide, LPS)-induced peritonitis [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the published pharmacokinetic studies in patients on APD, they were mostly conducted in patients without peritonitis (except vancomycin and amikacin). 5,6 Regarding antibiotic dosing recommendation in Table 5, the footnote ‘supplemental doses may be needed for APD patients’ applied to the table in general. 2 For some medications like vancomycin, we have provided specific additional information for APD.…”
mentioning
confidence: 99%